2022
DOI: 10.1007/s11655-022-3686-5
|View full text |Cite
|
Sign up to set email alerts
|

Active Ingredients of Reduning Injection Maintain High Potency against SARS-CoV-2 Variants

Abstract: The corona virus disease 2019 (COVID-19) pandemic has become a global health emergency. The spike protein (S-protein) of SARS-CoV-2, consisting of S1 and S2 subunits, is critical to receptor recognition and virus-cell fusion. SARS-CoV-2 binds to host cell receptors via the receptor-binding domain (RBD) of S1, which induces the formation of 6-helical bundle (6-HB) between the two heptad repeats (HRs) in S2, namely HR1 and HR2, and the consequential conformational change of S2, which facilitates the virus-membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Moreover, luteolin has been found to directly inhibit SARS‐CoV‐2 infection. In October 2022, Xiao et al (2022) demonstrated that luteolin, the main active component of redundancy injections, binds to the S‐protein of SARS‐CoV‐2 and inhibits its replication in BHK21‐hACE2 cells. In addition, luteolin inhibits the activities of the main protease (Chaves et al, 2022) and RNA‐dependent RNA polymerase (Munafò et al, 2022) of SARS‐CoV‐2, leading to the inhibition of viral replication in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, luteolin has been found to directly inhibit SARS‐CoV‐2 infection. In October 2022, Xiao et al (2022) demonstrated that luteolin, the main active component of redundancy injections, binds to the S‐protein of SARS‐CoV‐2 and inhibits its replication in BHK21‐hACE2 cells. In addition, luteolin inhibits the activities of the main protease (Chaves et al, 2022) and RNA‐dependent RNA polymerase (Munafò et al, 2022) of SARS‐CoV‐2, leading to the inhibition of viral replication in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudovirusbased assays have facilitated the screening of natural compounds for their ability to inhibit SARS-CoV-2 entry into host cells. Furthermore, pseudovirus technology has been crucial in studying the mechanisms of action of potential antiviral compounds against SARS-CoV-2 and its variants [60][61][62][63][64][65][66][67][68][69][72][73][74][75][76][77][78][79][80][82][83][84][85]. Luteolin-7-O-glucuronide (L7OG) and folic acid (FA) showed promising entry inhibitory activity against SARS-CoV-2 pseudotypes harboring alpha and omicron spike proteins [60].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a similar study was reported by Xiao, Z regarding SARS-CoV-2. A pseudovirus system tested the efficacy of quercetin and luteolin to inhibit SARS CoV-2 pseudovirus and genetic variants of SARS-CoV-2, including alpha variant B.1.1.7, beta variant B.1.351, delta variant B.1.617, and omicron [83].…”
Section: Natural Therapeutic Compounds Against Coronavirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, luteolin also inhibits RdRp activity [ 25 ]. Xiao et al, in a SARS-CoV-2 pseudovirus experiment, discovered that luteolin is able to bind to the S protein and significantly inhibits the entry of SARS-CoV-2 into cells with an EC50 less than 7 μmol/L [ 118 ]. COVID-19 can cause a loss of smell or taste.…”
Section: Anti-sars-cov-2 Activity Of Flavonoidsmentioning
confidence: 99%